Turbot (Scophthalmus maximus) NK-lysin induces broad-spectrum activity against parasites, bacteria and virus - Pereiro, Patricia; Falcó, Alberto; Lama, R.; Medina-Gali, Regla María; Bello Pérez, Melissa; Figueras Huerta, Antonio; Encinar, José Antonio; Novoa, Beatriz (2019)
19th International Conference on Diseases of Fish and Shellfish, Porto, 9th-12th September 2019 Nk-lysin (Nkl) is an antimicrobial peptide (AMP) belonging to the saposin-like protein (SAPLIP) family with ability to interact with biological membranes EU, Horizon 2020, ParaFishControl (project reference 634429) and the Spanish project BIO2017-82851-C3-1-R. Peer reviewed